PROFIL FINGERPRINTING KLT DAN PENENTUAN AKTIVITAS PENANGKAL RADIKAL BEBAS (DPPH) FRAKSI METANOL, ETIL ASETAT, DAN N-HEKSAN DAUN DADANGKAK (Hydrolea spinosa L.) - Dwi Rizki Febrianti; Desy Ayu Lestari PRAMUDITO; Rakhmadhan Niah PRAMUDITO; Eka Kumalasari; Inderiyani; Novia Ariani; Subagus Wahyuono; Siska Musiam (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Dadangkak leaves (Hydrolea spinosa L.) contain various secondary metabolites with potential antioxidant activity. This study aimed to evaluate the thin-layer chromatography (TLC) fingerprinting profile and antioxidant activity of the n-hexane, ethyl acetate, and methanol fractions of Dadangkak leaf extract. Extraction was performed using ethanol followed by fractionation based on solvent polarity. Compound profiling was analyzed by TLC under UV light at 254 and 366 nm using several spray reagents. Antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method with UV-Vis spectrophotometric measurement at 517 nm to determine IC₅₀ values. The results demonstrated that the methanol fraction exhibited the most comprehensive chromatographic profile, showing positive responses to all spray reagents, indicating a higher diversity of secondary metabolites compared with the other fractions. All fractions showed free radical scavenging activity against DPPH radicals. The IC₅₀ values were 0.110 ppm for the n-hexane fraction, 0.245 ppm for the ethyl acetate fraction, and −1.588 ppm for the methanol fraction. Furthermore, the methanol fraction showed the highest coefficient of determination (R²), indicating the strongest linear relationship between concentration and inhibition percentage. These findings suggest that the methanol fraction possesses the greatest potential as a natural antioxidant source.